Analysis Of Audience Reception To Youtube Content One Percent-Indonesian Life School (In The Video Susah Ngobrol Karena Pemalu? Cara Mengatasi Kecemasan Sosial) - Meytriantara, Rizky; Farida Nurfalah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Social media serves as a communication tool tailored to users' needs and as a platform for disseminating health education messages to internet users. Satu Persen – Indonesian Life School utilizes its YouTube account to convey messages focusing on education and lessons not taught in schools. In this study, Stuart Hall's theory is employed to analyze how audiences respond to the educational messages from Satu Persen – Indonesian Life School in the contexts of dominant hegemonic position, negotiated position, and oppositional position. The research findings indicate that the audience consuming content from the Satu Persen – Indonesian Life School YouTube account in the video "Susah Ngobrol Karena Pemalu? Cara Mengatasi Kecemasan Sosial" have varied receptions. Seventeen informants interpret the message in a dominant hegemonic manner, one informant negotiates the position, while none interpret the message in an oppositional hegemonic position. Most informants respond positively to the content presented by the Satu Persen – Indonesian Life School YouTube account because they are able to adapt media messages to their culture, perspectives, and personal experiences. Overall, the informants align with the message conveyed by the Satu Persen – Indonesian Life School YouTube account, although they adjust one part of the message to fit their personal context. The informants, as audience members of the Satu Persen – Indonesian Life School YouTube account, perceive the figures appearing in the video as experts in the field of education, represented through the shared video content on YouTube